The V5-Epitope Tag for Cell Engineering and Its Use in Immunohistochemistry and Quantitative Flow Cytometry - Katja Fritschle; Marion Mielke; Olga J. Seelbach; Ulrike Mühlthaler; Milica Živanić; Tarik Bozoglu; Sarah Dötsch; Linda Warmuth; Dirk H. Busch; Arne Skerra; Christian Kupatt; Wolfgang A. Weber; et al. (Biology)
Synthetic biology has fundamentally advanced cell engineering and helped to develop effective therapeutics such as chimeric antigen receptor (CAR)-T cells. For these applications, the detection, localization, and quantification of heterologous fusion proteins assembled from interchangeable building blocks is of high importance. The V5 tag, a 14-residue epitope tag, offers promising characteristics for these applications but has only rarely been used in this context. Thus, we have systematically evaluated the murine anti-V5 tag antibody mu_SV5-Pk1 as well as its humanized version, hu_SV5-Pk1, to analyze cells expressing V5-tagged receptors in samples from various in vitro and in vivo experiments. We found that the V5 tag signal on cells is affected by certain fixation and detachment reagents. Immunohistochemistry (IHC) on formalin-fixed paraffin-embedded (FFPE) mouse tissue samples was performed to sensitively detect cells in tissue. We improved IHC by applying the hu_SV5-Pk1 monoclonal antibody (mAb) to avoid cross-reactivity within and unspecific background signals arising on fixed mouse tissue. Conversely, the absence of unspecific binding by the mu_SV5-Pk1 mAb was evaluated on 46 human normal or cancer tissues. Our findings present a robust toolbox for utilizing the V5 tag and cognate antibodies in synthetic biology applications.